On Schools' Digital Transformation Readiness - Irina V. Dvoretskaya; Alexander Yu. Uvarov (Вопросы образования)
The schools’ digital transformation process is considered as an integral part of the digital renewal of education that started more than half a century ago. The digital renewal combines changes in the educational environment, content, methods and organizational forms of educational, as well as in the management system of an educational organization. The ICT harnessing is stimulated by the penetration of digital technologies into all spheres of society. To realize the schools' digital transformation successfully, it is necessary to determine to what extent the country’s schools are ready for transformational changes, to record the main differences between the upcoming changes and those that occurred during the development of digital technologies by schools in past years. The article presents the results of a study carried out as part of a project to monitor the digital transformation of educational organizations at the federal level, in which all regions of the country participated. The distribution of schools according to maturity levels is given, which are determined on the basis of a framework model of the process of digital school renewal. The groups of schools located at each level are described. It is shown that the indicators used today for the implementation of digital technologies in education (digital renewal of schools) make it possible to record innovative processes that occur at the initial stages of digital renewal. There is a need to develop indicators to recognize the changes occurring during the digital transformation and associated with the expansion of the traditional classroom system and the transition to a personalized learning system.